A CASE OF PERITONEAL SEROUS PAPILLARY ADENOCARCINOMA - UEDA, Koji; KOBASHI, Yuichi; USUI, Yoshiyuki; KAWAI, Toshinori; HIGASHI, Ryohei; NOMURA, Shuichi (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2003)
A 72-year-old woman was seen at the hospital because of right lower abdominal pain and abdominal distention. CT and magnetic resonance imaging scans revealed small quantities of fluid collection in the pouch of Douglas and a mass like omental cake beneath the wall of the lower abdomen. Aspiration cytology of the tumor showed adenocarcinoma, but no primary malignant tumor was detected on any organs. Peritonitis carcinomatosa of unknown origin was diagnosed, and an exploratory laparotomy was performed. There were serous ascites, a tumorous omentum, and widespread metastasis to the mesenterium, but the ovary and other abdominal organs were normal. Histology of the tumor showed serous papillary adenocarcinoma, which ordinary originates from the ovary. From these operative and histological findings, we diagnosed this case as peritoneal serous papillary adenocarcinoma (PSPC). She underwent chemotherapy with intravenous carboplatin and paclitaxel. Ascites and the omental tumor disappeared on CT. It is important to entertain PSPC as a differential diagnosis of peritonitis carcinomatosa with unknown origin.